Edukasi Pengelolaan Sampah Plastik Dari Rumah Tangga Menjadi Ecobrick - Titien Yusnita; Febri Palupi Muslikhah; Machyudin Agung Harahap (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
The problem of waste is always an interesting thing that never runs out to find a solution. One of them is plastic packaging waste that is widely used by the community and cannot be decomposed again by nature. In line with the SDGs issue, Indonesia is the second largest country that disposes of plastic waste in the world after China. This is very dangerous for the natural beauty of Indonesia's vast seas, and destroys a very diverse ecosystem. Existing plastic waste that comes from household waste, it can be used easily and cheaply into Ecobrick. Ecobrick is a term for the result of managing plastic waste into a brick that can be used as useful items such as chairs or tables. This plastic waste management training activity was carried out for housewives in Cibitung Tengah Village, Bogor Regency to find out the use of plastic waste that can be recycled to be used as useful goods. In addition, to provide awareness of the importance of sorting household waste in order to help preserve nature. Keywords: ecobricks, management, household, plastic waste